Application progress of human amniotic membrane in vitreoretinopathy: a literature review - Yang, Huawei; Li, Ziyue; Jin, Wei; Yang, Anhuai (Frontiers in Medicine, 2023)
Recently, the application of the amniotic membrane (AM) in ophthalmology is gradually expanding from the anterior to the posterior segment of the eye. Its characteristics of anti-inflammation, anti-bacterial, anti-vascularization, immune regulation, anti-fibrosis, pro-epithelialization, and so forth have made it a hot topic in ophthalmic research. AM has been confirmed to repair photoreceptors, restore normal retinal structures, and close the abnormal structures in the optic disc. Currently, the application areas mainly include retinal hole, retinal detachment, optic disc pit, retinal degenerative diseases, and choroidal hole. This article reviews the current literature applying AM transplantation in the treatment of various posterior segment diseases while comparing the clinical outcomes with other techniques.